PERBANDINGAN KADAR KARBON MONOKSIDA (CO) DAN NITROGEN DIOKSIDA (NO2) DI UDARA AMBIEN BERDASARKAN KEBERADAAN POHON ANGSANA (Pterocarpus indicus) DI BEBERAPA JALAN RAYA DI KOTA MEDAN TAHUN 2012 - Yenni Yulfida Harahap; Irnawati Marsaulina; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2013)
Comparison levels of carbon monoxide (CO) and nitrogen dioxide (NO2) in the ambient air depend on of Angsana tree (Pterocarpus indicus) in the some road in Medan city in 2012. The main pollutant produced by vehicles is carbon monoxyde (CO) and nitrogen dioxyde (NO2). Carbon monoxida (CO) and nitrogen dioxyde (NO2) is a parameter change in air quality, in case of eleveted levels of this materials in the air exceeds the quality standars that have been set can cause health problems for humans. The aim of this research was analyize concentrate of carbon monoxyde (CO) and nitrogen dioxyde (NO2) ambient on highways based on the existence of Angsana tree (Pterocarpus indicus). The result of research the highest concentration of carbon monoxyde (CO) was found on the highways planted Angsana (Pterocarpus indicus) is Jl. A.H Nasution and on highways that are not planted Angsana (pterocarpus indicus) is Jl. Asia 16.033 ug/Nm³ and the lowest concentratin of carbon monoxyde (CO) was found on the highways planted Angsana (pterocarpus indicus) is Jl. Brigjend Katamso 4.581 ug/Nm³. The highest concentration of nitrogen dioxyde (NO2) was found on the highways are not planted Angsana (Pterocarpus indicus) is Jl. S. Parman 29,78 ug/Nm³ and the lowest concentration of nitrogen dioxyde (NO2) was found on the highway planted Angsana (Pterocarpus indicus) is Jl. A.H Nasution 9,22 ug/Nm³. In could be concluded that concentration of carbon monoxyde (CO) on the highway planted Angsana trees (Pterocarpus indicus) and on roads in which there was no Angsana tree planted was similar, the highest concentration of nitrogen dioxyde (NO2) was found on the highway that are not planted Angsana tree (Pterocarpus indicus) planted. For the reason, it would be nescessary to grow some trees that can absorb excessive gas carbon monoxyde (CO) and nitrogen dioxide (NO2) especially on roads in which the passing through vehicles are very active. Keywords: CO concentration, NO2 concentration, Angsana, the Street